Optimization model for the installation of SAMU bases: application in Natal-RN - dos Santos Cabral, Eric Lucas; Silva Castro, Wilkson Ricardo; Cavalheiro Francisco, Claudia Aparecida; Pires de Souza, Ricardo (Revista Gestão da Produção Operações e Sistemas, 2019)
A Medical Emergency Service is responsible for providing pre-hospital acute care and has the key role of providing good services to people, especially in urban areas. In Brazil, the Emergency Medical Assistance Service (SAMU) operates in several cities and aims to reach the victim early after an injury to his health has occurred, by sending vehicles manned by trained personnel. The objective of this study was the application of a mathematical model aiming to designate neighborhoods for the installation of new SAMU bases that minimize the distance traveled by the ambulances in the city of Natal / RN. After data collection, it was found that the average service response time of the SAMU was over 40 minutes for calls classified as red code. The average number of calls in 2015 was 1,930 per month, in this city with a population of 800,000. The application of the model allowed for the simulation of scenarios with the installation of 3 to 8 fixed bases. There was a significant reduction in the distance traveled by the ambulances which reached 48%, after the installation of eight bases. In other words, there was a reduction of 6,560 kilometers traveled per month by ambulances. The new SAMU bases are being installed in containers to minimize installation costs and easy relocation in the near future.